WOUTERS, Jan; VERHEY, Luc y KIIVER, Philipp (eds.) (2009). European Constitutionalism Beyond Lisbon. Antwerp. Países Bajos: Intersentia Ltd (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2010)
Recensión de la obra: WOUTERS, Jan; VERHEY, Luc y KIIVER, Philipp (eds.) (2009). European Constitutionalism Beyond Lisbon. Antwerp. Países Bajos: Intersentia Ltd.